POLA PEMBINAAN PONDOK PESANTREN AL-HUDA PROVINSI GORONTALO DALAM MENINGKATKAN PENGUASAAN SANTRI TERHADAP KITAB KUNING - Abd. Rasyid Kamaru (Pascasarjana IAIN Sultan Amai Gorontalo, 2016)
The pattern of Al-Huda pesantren cultivation in Gorontalo province shows encouraging results because the uniqueness of education system in boarding school such as pesantren al-Huda pondok focuses on the balance of science and technology achievement and IMTAQ this can be seen from the application of 3 curriculum models namely national curriculum, religious ministry curriculum , and curriculum of boarding school. The uniqueness of education system in boarding school is also followed by educating teachers. It can be seen from the state of ustadz / teacher who teaches at boarding school not only comes from governmental institution but also comes from alumni of boarding school which is expected with experience of boarding life life at boarding school before, can become role model for santri.